Динаміка вмісту флавоноїдів у надземних органах сортів і форм Asimina triloba (L.) Dunal - Levon, V.F.; Klymenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Pawpaw three-blade (Asimina triloba (L.) Dunal) is the new plant introduced from North America into different regions of Ukraine. The pawpaw is widely cultivated in many countries of Europe as a valuable food, medicinal and ornamental plant. In the conditions of an introduction in Ukraine adaptation properties of a pawpaw at the biochemical level weren't studied. One of important indicators of adaptation of plants is accumulation of flavonoids, secondary metabolites of the phenolic nature. Flavonoids show multifunctional action in plants, participating in many processes of activity, play an important role in processes of formation of reproductive organs and immunity of plants. Results of researches of dynamics of accumulation of flavonoids at pawpaw cultivars and forms in the South and the North of Ukraine at stages of the major processes of activity – during active growth, blossoming, maturing of fruits and in the course of preparation of plants for organic rest are covered in article. As showed researches, the content of flavonoids as indicator of accumulation of secondary metabolites, though have no crucial importance in the course of complex adaptation, however they are an indicator of biochemical transformations and balance of processes of changes in specific ecological conditions and reflect information about the preadaptation processes of acclimatization of plants in the conditions of an introduction.